2014
DOI: 10.1002/smll.201303951
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Delivery of Doxorubicin and siRNA with Reduction and pH Dually Sensitive Nanocarrier for Synergistic Cancer Therapy

Abstract: Drug resistance is the greatest challenge in clinical cancer chemotherapy. Co-delivery of chemotherapeutic drugs and siRNA to tumor cells is a vital means to silence drug resistant genes during the course of cancer chemotherapy for an improved chemotherapeutic effect. This study aims at effective co-delivery of siRNA and anticancer drugs to tumor cells. A ternary block copolymer PEG-PAsp(AED)-PDPA consisting of pH-sensitive poly(2-(diisopropyl amino)ethyl methacrylate) (PDPA), reduction-sensitive poly(N-(2,2'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 31 publications
0
106
0
Order By: Relevance
“…The biodegradable nano-carriers have intense potential to deliver two or more drugs. Co-delivery using a single nano-carrier ensures the controlled drug ratios, same drug disposition behavior and hence maximizing the therapeutic efficacy [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The biodegradable nano-carriers have intense potential to deliver two or more drugs. Co-delivery using a single nano-carrier ensures the controlled drug ratios, same drug disposition behavior and hence maximizing the therapeutic efficacy [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…[94] In this study, pH/reduction dual-responsive nanoparticles that were self-assembled from triblock PEG-b-poly(N-(2,2′-dithiobis(ethylamine)) aspartamide)-b-poly(2-(diisopropyl amino) ethyl methacrylate) (PEG-b-PAsp(AED)-b-PDPA) copolymer were evaluated as intelligent carriers for combination cancer therapy (Figure 8). DOX was loaded into the pH-responsive PDPA core and could be released under an acidic environment, while Bcl-2 siRNA was encapsulated into the PAsp(AED) middle layer and could be released under a reductive environment.…”
Section: Polypeptide-based Drug/gene Co-delivery Systemsmentioning
confidence: 99%
“…Attributing to the downregulation of anti-apoptotic BCL-2 protein expression by Bcl-2 siRNA as well as the synergistic therapeutic effect, this polyaspartamide-based co-delivery system significantly inhibited the growth of human ovarian cancer in animal models. [94] 3.5. Natural Polymers-Based Drug/Gene Co-Delivery Systems Naturally occurring polymers offer many advantages over synthetic polymers in biomedical applications because of their low cost and outstanding biocompatibility.…”
Section: Polypeptide-based Drug/gene Co-delivery Systemsmentioning
confidence: 99%
“…For example, it has been demonstrated that combining a chemotherapeutic agent with siRNA in a co-delivery nanocarrier can significantly enhance therapeutic efficacy. [20][21][22][23] In the past few decades, many efforts have been made to improve the solubility, stability, and pharmacokinetics of small molecule organic drugs with the aid of cyclodextrins (CDs) and their derivatives. The hydrophobic internal cavity of CDs endows them with the capability to form inclusion complexes with organic drugs, and their hydrophilic exterior (due to the presence of hydroxyl radicals) guarantees good water solubility of the complexes.…”
Section: Introductionmentioning
confidence: 99%